Does Health Contribute to Economic Growth? An Evidence from Regional Levels in Indonesia - Vita Kartika Sari; Malik Cahyadin; Aranka Ignasiak-Szulc (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2022)
Health can lead economic development in many countries. The higher the quality of health, the more space for increasing economic growth and providing prosperity in the long-run. The current study attempts to estimate the effect of health on regional economic growth in Indonesia. Balanced panel data is set covering 34 provinces from 2015 to 2020. The panel data is estimated using system Generalized Method of Moments (GMM). The findings reveal that smoking level contributes significantly and positively on regional economic growth, while health service has no effect. The non-linear impact of smoking level on regional economic growth is U-shaped. It means that higher smoking level stimulates regional economic growth by the increasing of aggregate spending. The local governments should design health service program and control smoking level properly so that the health risk of cigarette consumption does not offset its benefit to the economy. The policy design will produce better human health and life in all provinces in Indonesia. Consequently, the regional economic growth can be achieved in the long-run.